Selective hydrogen production from formic acid decomposition over Mo carbides supported on carbon materials. Issue 20 (10th August 2020) - Carrales-Alvarado, D. H.; Dongil, A. B.; Fernández-Morales, J. M.; Fernández-García, M.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract : The support influenced the carbide phase obtained so that a higher ratio of defective carbon favoured the formation of β-Mo2 C phase vs. MoO x C y . Redox transformations during the reaction might be responsible of the transformation of β-Mo2 C into MoO x C y . Abstract : The decomposition of formic acid to obtain hydrogen has been studied using molybdenum carbides supported on activated carbon and two high surface area graphites, H200 (200 m 2 g −1 ) and H400 (400 m 2 g −1 ). Particular attention is paid to the effect of Mo loading. The catalysts were prepared in situ using a mixture of CH4 and H2 at a temperature of up to 700 °C. Under these conditions, carburization was mostly complete. We observed that the support influenced the Mo x C phase obtained so that it seems that the ratio of defective carbon influences the phase. However, for these materials the C/Mo ratio did not influence the obtained crystal phase. Characterization by XRD showed that while the β-Mo2 C phase was obtained over activated carbon and over H200, in contrast, MoO x C y was obtained over H400 . These catalysts reached 100% conversion on formic acid decomposition at temperatures in the range of 190–250 °C and were also highly selective under these mild conditions, with values for CO2 selectivity in the range of 85.0–96.5%. The best results were achieved over a 10 wt% Mo loading on activated carbon that reached 96.5% selectivity to H2 . Also, changes in the molybdenum phases were observed on the spent catalyst. Some redox transformations during reaction were responsible for the transformation of β-Mo2 C into oxycarbide MoO x C y . In summary, the results of the catalytic performance indicated that the β-Mo2 C phase was more active, selective and stable than MoO x C y under the studied conditions.